Pengaruh Pelatihan Dan Kompetensi Terhadap Kinerja Pegawai Pada Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Bekasi - Cindy Ayu Lestari; Anggi Pasca Arnu (COSTING : Journal of Economic, Business and Accounting, 2021)
The purpose of training is to improve employee competence, so that employees who have inadequate abilities or skills can be provided with training, are friendly in order to boost employee performance to be better. So it means that training and talent competencies greatly affect employee performance. Research methods are activities in the form of data analysis and providing interpretations related to the research objectives. The independent variables are competence and training with the variables served are employee performance. Respondents of this study were employees of the Bekasi District Development Planning Agency (BAPPEDA). The results of the research had a positive and partially significant effect on performance, which had a positive and partially significant effect on performance and independent variables, namely training (X1) and competence (X2) simultaneously. positive and significant effect on performance (Y). Keywords: Training, Competence, Performance.